Spektroskopische und theoretische Untersuchungen zu Struktur und Dynamik von kovalenten Fulminaten und Heterokumulenen - Lichau, Holger; Justus Liebig University Giessen (My University, 1999)
The a-type rotational spectra of the covalent fulminates BrCNO, ClCNO, and NCCNO have been investigated by millimeterwave spectroscopy. Owing toextremely anharmonic XCN bending modes, the a-type rotational spectra of the halofulminates BrCNO and ClCNO exhibited very unusual patterns, whereasthe low-lying CCN bending mode of cyanofulminate NCCNO appeared to be close to a harmonic bending mode of a linear molecule. This has been confirmedby a rovibrational spectrum of the CCN band system in the far infrared. The data for NCCNO have been analyzed with a linear molecule type hamiltonian,resulting in precise term values for the first to the fifth excited state of the CCN bending mode. The fundamental transition wavenumber has been determined tobe 80.5242 cm-1. From semirigid bender analyses, effective barriers to linearity of 131 cm-1 for BrCNO and 167 cm-1 for ClCNO have been obtained. ForNCCNO, a relatively flat bending potential with a significant quartic contribution has been found. Compared to the parent molecule, the well-known quasilinearmolecule fulminic acid HCNO, the halofulminates BrCNO and ClCNO are considerably 'more bent', whereas cyanofulminate NCCNO is definitely 'morelinear'. Barriers to linearity in covalent fulminates XCNO apparently strongly depend on the nature of the substituent X: pi-acceptor substituents lead to 'morelinear' molecules, whereas pi-donor substituents result in 'more bent' molecules. This assumption has been confirmed by large-scale ab-initio calculations.
Keywords: ddc:540